Morpho-phenotypic characterization of melanoma brain metastases immune microenvironment: A multicentre retrospective study - Filippo Nozzoli; Marco Gessi; Filippo Ugolini; Sara Simi; Luca Tinunin; Luigi Francesco Iannone; Alice Esposito; Giovanni Muscas; Alessandro Della Puppa; Isabella Ciardetti; Nicola Pimpinelli; Vincenzo De Giorgi; et al. (EJC Skin Cancer)
Introduction: The recent rise of immunotherapy for melanoma brain metastases (MBM) has enhanced the interest in characterizing the composition of local immune microenvironment. Despite the central nervous system (CNS) is well known for harbouring a peculiar immunological milieu, its role in MBM is only partially understood. The aim of our study was to characterize tumour-infiltrating lymphocytes (TILs) and tumour-associated macrophages (TAMs) distribution and density in a cohort of MBM and their potential relevance as prognostic biomarkers. Materials and methods: Ninety-four MBM patients were retrospectively evaluated for morphological, molecular features and follow-up data. Formalin-fixed and paraffin-embedded (FFPE) tissue sections were immunostained with the following antibodies: CD4, CD8, FoxP3 CD68, CD163, PD-L1, HLA-ABC. Semiquantitative assessment of TILs and TAMs density and spatial distribution was performed and statistical analysis for prognostic correlations was carried out. Results: The distribution of CD4+ TILs was higher in the intratumoral region (p=0.012) while CD163+ TAMs in the peritumoral (p=0.016). An association was also found between tumour-associated astrogliosis (TAA) and CD163+ TAMs (p=0.021). Increased CD68+ TAMs correlated with BRAF V600 mutation (p=0.038). CD4+ TILs were significantly higher in PD-L1 <1 % group (p=0.030). CD68+ high expression group significantly correlated with PD-L1 ≥1 % (p=0.029). Median HLA-ABC H-score was significantly associated with intratumoral CD4+ (p=0.005) and peritumoral CD8+ infiltration (p=0.048). CD68+ TAMs intratumoral high expression showed a favorable association with OS in patients with multiple MBM (p=0.017), whereas a high HLA-ABC H-score with a prolonged OS in those with single MBM (p=0.007). Conclusions: Our findings suggest a peculiar topographical distribution of immune cells in both intratumoral and peritumoral areas, and correlations with both BRAF V600 mutation and PD-L1 expression in a large cohort of MBM. Moreover, CD68+ TAMs distribution and HLA-ABC favourably impacted prognosis in patients with multiple and single brain metastases, respectively.